ASSESSMENT OF THE QUALITY OF MANAGEMENT OF REGIONAL FINANCES ON THE EXAMPLE OF STAVROPOL REGION - I. Alimova; D. Telichko (Вестник Северо-Кавказского федерального университета, 2022)
Category «quality» is a set of properties, features of an object, which determines their ability to meet the needs of users, to meet its purpose and requirements. And the quality of management reflects the completeness of all the advantages, the highest degree of management at all levels of the system, including the management of regional budget. In the article the authors consider the general methodological basics for assessing the quality of regionalfinance management, as well as the analysis of the quality of financial management of the Stavropol region. The problems and shortcomings in the implementation of budget legislation were identified.